The HIV-derived protein Vpr 52-96 has anti-glioma activity in vitro and in vivo - Kübler, Jens; Kirschner, Stefanie; Hartmann, Linda; Welzel, Grit; Engelhardt, Maren; Herskind, Carsten; Veldwijk, Marlon Romano; Schultz, Christian; Felix, Manuela; Glatting, Gerhard; Maier, Patrick; Wenz, Frederik; et al. (OncoTarget, 2016)
Patients with actively replicating human immunodeficiency virus (HIV) exhibit adverse reactions even to low irradiation doses. High levels of the virus-encoded viral protein R (Vpr) are believed to be one of the major underlying causes for increased radiosensitivity. As Vpr efficiently crosses the blood-brain barrier and accumulates in astrocytes, we examined its efficacy as a drug for treatment of glioblastoma multiforme (GBM). In vitro, four glioblastoma-derived cell lines with and without methylguanine-DNA methyltransferase (MGMT) overexpression (U251, U87, U251-MGMT, U87-MGMT) were exposed to Vpr, temozolomide (TMZ), conventional photon irradiation (2 to 6 Gy) or to combinations thereof. Vpr showed high rates of acute toxicities with median effective doses of 4.0±1.1 μM and 15.7±7.5 μM for U251 and U87 cells, respectively. Caspase assays revealed Vpr-induced apoptosis in U251, but not in U87 cells. Vpr also efficiently inhibited clonogenic survival in both U251 and U87 cells and acted additively with irradiation. In contrast to TMZ, Vpr acted independently of MGMT expression. Dose escalation in mice (n=12) was feasible and resulted in no evident renal or liver toxicity. Both, irradiation with 3x5 Gy (n=8) and treatment with Vpr (n=5) delayed intracerebral tumor growth and prolonged overall survival compared to untreated animals (n=5; p3x5 Gy<0.001 and pVpr=0.04; log-rank test). Our data show that the HIV-encoded peptide Vpr exhibits all properties of an effective chemotherapeutic drug and may be a useful agent in the treatment of GBM.
Gesehen am 08.07.2019
Im Titel ist "52-96" tiefgestellt